Monitoring and modulating a catalytic hybridization circuit for self-adaptive bioorthogonal DNA assembly. Issue 35 (24th August 2022) - Gong, Xue; He, Shizhen; Li, Ruomeng; Chen, Yingying; Tan, Kaiyue; Wan, Yeqing; Liu, Xiaoqing; Wang, Fuan
Abstract : A localized catalytic circuit, facilitating the self-assembly of DNA nanosponges, is developed for robust and accurate monitoring of miRNA targets in live cells and mice. Abstract : Constructing artificial domino nanoarchitectures, especially dynamic DNA circuits associated with the actuation of biological functions inside live cells, represents a versatile and powerful strategy to regulate the behaviors and fate of various living entities. However, the stepwise operation of conventional DNA circuits always relies on freely diffusing reactants, which substantially slows down their operation rate and efficiency. Herein, a self-adaptive localized catalytic circuit (LCC) is developed to execute the self-sustained bioorthogonal assembly of DNA nanosponges within a crowded intracellular environment. The LCC-generated DNA scaffolds are utilized as versatile templates for realizing the proximity confinement of LCC reactants. Single-molecule-detecting fluorescence correlation spectroscopy (FCS) is used to explore the reaction acceleration of the catalytic circuit. This self-adaptive DNA circuit facilitates the bioorthogonal assembly of highly branched DNA networks for robust and accurate monitoring of miRNA targets. Based on its intriguing and modular design, the LCC system provides a pivotal molecular toolbox for future applications in early disease diagnosis.